Small business manegement and entrepreneurship - Stokes, David; Wilson, Nicholas (Andover : Cengage Learning Asia Pte Ltd, 2010)
This text explores the contexts, choices and strategies facing the small business venture, including coverage of planning a new venture. It contains pedagogical features that include case material to explore the same case situation from a number of different but interrelated angles and chapter-end real world case studies.
Part 1. Understanding small business and entrepreneurship -- 1. Small business in the economy -- 2. Entrepreneurship, the entrepreneur and the owner-manager -- 3. The small business and entrepreneurial environment -- 4. Innovation and the marketplace -- 5. Information and help -- Part 2. Creating the entrepreneurial small business -- 6. Business planning -- 7. Successful small business strategies -- 8. Start ups and franchises -- 9. Buying an existing business -- 10. Forming and protecting a business -- Part 3. Managing the entrepreneurial small business -- 11. Management of people and resources -- 12. Marketing -- 13. Money -- 14. Business exits and realizing value.
Includes index.
Keywords: SMALL BUSINESS -- MANAGEMENT